Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 3x+1 =279
=> 3x * 31 = (33)9 = 3 3 x 9 = 327
=> 3x = 327 : 31 = 326
=> 3x = 3 26
=> x= 26
b) ( x - 1 ) 5 = 32
=> ( x - 1 )5 = 25
=> x - 1 = 2
=> x = 2 + 1 = 3
c) 2 x = 815
=> 2x =( 24)15
=> 2x = 2 4 x 15 = 2 60
=> 2x = 260 => x=60
a)x3=125
x3=53
=>x=5
Vậy x=5
b)(x-1)3=27
(x-1)3=33
=>x-1=3
x=3+1
x=4
Vậy x=4
c)4x=16
4x=42
=>x=2
Vậy x=2
d)3x=81
3x=34
=>x=4
Vậy x=4
d)x5=32
x5=25
=>x=2
Vậy x=2
C2 :
\(2\cdot3^{x+2}+4\cdot3^{x+1}=10\cdot3^{2019}\)
\(2\cdot3\cdot3^{x+1}+4\cdot3^{x+1}=10\cdot3^{2019}\)
\(6\cdot3^{x+1}+4\cdot3^{x+1}=10\cdot3^{2019}\)
\(\left(6+4\right)\cdot3^{x+1}=10\cdot3^{2019}\)
\(10\cdot3^{x+1}=10\cdot3^{2019}\)
\(\Rightarrow x+1=2019\)
\(x=2019-1\)
\(x=2018\)
Vậy x = 2018
Chắc sai =))
e)\(\left(x-5\right)^5=32\)
\(\left(x-5\right)^5=2^5\)
\(\Rightarrow x-5=2\)
\(\Rightarrow x=7\)
f)\(\left(2-x\right)^4=81\)
\(\left(2-x\right)^4=3^4\)
\(\Rightarrow2-x=3\)
\(\Rightarrow x=-1\)
a) 3x = 32 . 33
3x = 35
=> x = 5
b)5x =125 .25
5x = 53 . 52
5x = 55
=> x = 5
c) 8 =2x
23 = 2x
=> x = 3
d) x = 4
e)x = 3
f)x = 4
\(9^x:3^{x+9}=27\)
\(9^x=27\cdot3^{x+9}\)
\(\left(3^2\right)^x=3^3\cdot3^{x+9}\)
\(3^{2x}=3^{x+12}\)
\(\Rightarrow2x=x+12\)
\(2x-x=12\)
\(x=12\)
\(4^{x+y}:2^{5y}=32\)
\(4^{12+y}=32\cdot2^{5y}\)
\(\left(2^2\right)^{12+y}=2^5\cdot2^{5y}\)
\(2^{24+2y}=2^{5+5y}\)
\(24+2y=5+5y\)
\(24-5=5y-2y\)
\(3y=19\)
\(y=19:3\)
\(y=\frac{19}{3}\)
Vậy \(x=12;y=\frac{19}{3}\)
Ta có: \(\frac{9^x}{3^{x+9}}=27\)
\(\Leftrightarrow3^{2x}=3^{x+9}\cdot3^3\)
\(\Leftrightarrow3^{2x}=3^{x+12}\)
\(\Rightarrow2x=x+12\)
\(\Rightarrow x=12\)
Thay vào: \(\frac{4^{12+y}}{2^{5y}}=32\)
\(\Leftrightarrow2^{2y+24}=2^{5y}\cdot2^5\)
\(\Leftrightarrow2^{2y+24}=2^{5y+5}\)
\(\Rightarrow2y+24=5y+5\)
\(\Leftrightarrow3y=19\)
\(\Rightarrow y=\frac{19}{3}\)
Vậy \(\hept{\begin{cases}x=12\\y=\frac{19}{3}\end{cases}}\)
=> [3x-7/9]^3= -8/27
=> 3x -7/9 = -2/3 => 3x = 1/9=> x= 1/27
đúng cái nhé
x^3 - 27 + 32 = 69
x^3 - 27 =69 -32
x^3 - 27 =37
x^3 =37+27
x^3 =64
Vì x^3 =4^3
Suy ra x = 4
Vậy x = 4
x3 - 27 + 32 = 69
x3 - 27 = 69 - 32
x3 - 27 = 37
x3 = 37 + 27
x3 = 64
x3 = 43
x = 4